Chlorophyll Synthesis in Chlorella I. Occurrence of a Lag Phase on Initiation of a Dilute Culture - Shugarman, Peter M. (1966)
A culture of Chlorella established by 30-fold dilution of a culture already grown to a level of 15 ml packed cell volume per liter produces little chlorophyll for approximately 12 hours. Investigation of other characteristics such as nitrogen incorporation, increase in packed cell volume and dry weight as well as RNA level show all of these to increase without any significant lag. α-Linolenate, which can be considered as a chloroplast marker, increased markedly. Photosynthetic oxygen evolution and respiration as well as the heme enzyme, catalase, increase also, indicating that the lag in chlorophyll synthesis is not due to a general inability to produce the porphyrin moiety. The lag period was demonstrated not to be related to a deficiency of culture elements nor to inhibitors produced. Neither was there a need for a conditioning period of the medium. It is concluded that the lag in chlorophyll synthesis is unique and that the reasons for it are related to the response of the cells to environmental conditions following dilution.